In how many ways may a health research go wrong? - Nagesh Lakshminarayan (Wolters Kluwer Medknow Publications, 2016)
Research, in the broadest sense, includes gathering of data, information and facts for the advancement of knowledge. It is a systematic investigation done in order to establish or confirm facts, reaffirm the results of previous work, solve new or existing problems, support theorems, or develop new theories. A good research is an offshoot of a good design. Research (study or experimental) design is the backbone of good research. It is the framework that has been created to seek answers to research questions. Designing a research project takes time, skill and knowledge. If designing is not done scrupulously, errors may creep into the research at various stages of planning, designing, conducting, analyzing, reporting, and publishing of research output. These errors may distort the results leading to invalid conclusions. The only way to not let these errors occur is to avoid them to the maximum possible extent by gaining comprehensive knowledge about each error and applying measures to control and minimize them. Perfect health research does not exist but a high quality research certainly exists.